1997
DOI: 10.1212/wnl.48.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Alzheimer's disease and duration of NSAID use

Abstract: In a longitudinal study of 1,686 participants in the Baltimore Longitudinal Study of Aging, we examined whether the risk of Alzheimer's disease (AD) was reduced among reported users of aspirin or other nonsteroidal anti-inflammatory drugs (NSAIDs). In addition, we examined use of acetaminophen, a pain-relief medication with little or no anti-inflammatory activity, to assess the specificity of the association between AD risk and self-reported medications. Information on use of medications was collected during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
578
4
12

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,040 publications
(616 citation statements)
references
References 10 publications
17
578
4
12
Order By: Relevance
“…Therefore, COX inhibitors may be useful drugs to treat or retard the progression of Alzheimer's disease. Numerous clinical trials have examined the therapeutic benefit of COX inhibitors in Alzheimer's patients with the best success in patients treated early during disease progression and when used for more than 24 months (Stewart et al, 1997;in't Veld et al, 2001). Similarly, animal studies with aged rats demonstrate that PGs can be elevated with normal aging and COX inhibitors can reverse age-related memory impairments (Casolini et al, 2002;Mesches et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, COX inhibitors may be useful drugs to treat or retard the progression of Alzheimer's disease. Numerous clinical trials have examined the therapeutic benefit of COX inhibitors in Alzheimer's patients with the best success in patients treated early during disease progression and when used for more than 24 months (Stewart et al, 1997;in't Veld et al, 2001). Similarly, animal studies with aged rats demonstrate that PGs can be elevated with normal aging and COX inhibitors can reverse age-related memory impairments (Casolini et al, 2002;Mesches et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that inflammatory processes play an active role in AD; epidemiological studies reported that the use of nonsteroidal anti-inflammatory drugs is associated with marked reduction in the risk of AD ( [106,154,156,219,225]). Following this initial observation, additional reports were published that witnessed the involvement of neuroinflammation in AD pathogenesis and progression.…”
Section: Alzheimer's Disease and Neuroinflammationmentioning
confidence: 99%
“…[85][86][87][88] Some also argue that NSAIDs have no effect in patients already suspected to have developed AD 89 and that treatment with a COX-2 inhibitor increases the amount of b-amyloid found in the brain. 90 One must note that inhibition of COX-2 in the CNS has proinflammatory properties.…”
Section: Innate Immunity and Alzheimer's Diseasementioning
confidence: 99%